2019–2020 Florida Citrus Production Guide: Fresh Fruit Pesticide Residue Limits - Mark A. Ritenour (EDIS)
This 5-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Mark A. Ritenour and published by the Horticultural Sciences Department, March 2019.